2004
DOI: 10.1046/j.1600-6143.2003.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ CD25+ CD62+ T-Regulatory Cell Subset Has Optimal Suppressive and Proliferative Potential

Abstract: CD4 + CD25 + regulatory T cells (Treg) are potent suppressors, and play important roles in autoimmunity and transplantation. Recent reports suggest that CD4 + CD25 + Treg are not a homogeneous cell population, but the differences in phenotype, function, and mechanisms among different subsets are unknown. Here, we demonstrate CD4 + CD25 + Treg cells can be divided into subsets according to cell-surface expression of CD62L. While both subsets express foxp3 and are anergic, the CD62L + population is more potent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
133
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 71 publications
13
133
0
2
Order By: Relevance
“…CCR4 expression may drive Treg cells to sites of antigen presentation (such as the skin in BP patients) supporting the down-regulation ofT-cell activation [17]. As to CD62L expression, CD4+ CD25bright nTregs positive for L-selectin display a significantly stronger suppressor activity than the negative ones [15,29]. Taken together, the CD4+ CD25bright-FOXP3+ cells shown to be reduced in BP patients exhibited the Tregs characteristic phenotypic features.…”
Section: Discussionmentioning
confidence: 89%
“…CCR4 expression may drive Treg cells to sites of antigen presentation (such as the skin in BP patients) supporting the down-regulation ofT-cell activation [17]. As to CD62L expression, CD4+ CD25bright nTregs positive for L-selectin display a significantly stronger suppressor activity than the negative ones [15,29]. Taken together, the CD4+ CD25bright-FOXP3+ cells shown to be reduced in BP patients exhibited the Tregs characteristic phenotypic features.…”
Section: Discussionmentioning
confidence: 89%
“…It has been suggested that the CD62L high population has greater suppressive capacity. 38 The number of isolated TILs was small, so TGF-␤1 expression was studied in only 3 patients. A proportion of CD4 ϩ CD25 ϩ cells expressed active TGF-␤1 on the membrane (35.6%, 8%-63%; n ϭ 3; see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, depletion of this regulatory subset induces the spontaneous onset of various autoimmune disorders (19). Several important molecules, such as glucocorticoid-induced tumor necrosis factor receptor, CTLA-4, TGF-␤, CD62L, CD45Rb low , Foxp3, and neuropilin, have emerged as markers of this unique T cell lineage (20)(21)(22)(23)(24)(25)(26). These cells act by suppressing the cytokine production and proliferation of conventional CD4 ϩ CD25 Ϫ T cells as well as that of CD8 ϩ T cells.…”
mentioning
confidence: 99%